Weight loss as a predictor of cancer in primary care: a systematic review and meta-analysis - Nicholson, B; Hamilton, W; O'Sullivan, J; Aveyard, P; Hobbs, F (Royal College of General Practitioners, 2018)
Background Weight loss is a non-specific cancer symptom for which there are no clinical guidelines about investigation in primary care. Aim To summarise the available evidence on weight loss as a clinical feature of cancer in patients presenting to primary care. Design A diagnostic test accuracy review and meta-analysis. Methods Studies reporting 2 × 2 diagnostic accuracy data for weight loss (index test) in adults presenting to primary care and a subsequent diagnosis of cancer (reference standard) were included. QUADAS-2 was used to assess study quality. Sensitivity, specificity, positive likelihood ratios, and positive predictive values were calculated, and a bivariate meta-analysis performed. Results A total of 25 studies were included, with 23 (92%) using primary care records. Of these, 20 (80%) defined weight loss as a physician’s coding of the symptom; the remainder collected data directly. One defined unexplained weight loss using objective measurements. Positive associations between weight loss and cancer were found for 10 cancer sites: prostate, colorectal, lung, gastro-oesophageal, pancreatic, non-Hodgkin’s lymphoma, ovarian, myeloma, renal tract, and biliary tree. Sensitivity ranged from 2% to 47%, and specificity from 92% to 99%, across cancer sites. The positive predictive value for cancer in male and female patients with weight loss for all age groups ≥60 years exceeded the 3% risk threshold that current UK guidance proposes for further investigation. Conclusion A primary care clinician’s decision to code for weight loss is highly predictive of cancer. For such patients, urgent referral pathways are justified to investigate for cancer across multiple sites.